Profiling sustainable visitors to boost sustainable tourism in Spain - Joana Longo-Sarachaga; María del Carmen Paradinas Márquez (Discover Sustainability)
Abstract In addition to having significant effects on social and environmental aspects, tourism is essential to the global economy. In this regard, tourism is a remarkable factor that should be considered in the pursuit of sustainable development. Among the influencing factors in this sector, visitors are most notable. In accordance with the World Tourism Organization (WTO) requirements for more sustainable tourism, this study attempts to describe the ideal consumer profile of sustainable visitors. Spain was chosen as a case study since it is one of the most popular travel destinations in the world. Boomers, Gen Xers, Millennials, and Centennials were identified as potential tourism consumers using a mixed methodology comprising a literature review, content analysis and a questionnaire distributed among 120 scholars from Spanish institutions. Each generation consumer’s profile differs significantly from the others. Results indicated that the impact of WTO standards in encouraging more environmentally friendly travel is debatable.